Investigating the Effect of Using Audiovisual Aids in Improving EFL Students' Vocabulary Retention A Case Study of First-Year EFL Students of English at Mohamed-Cherif Messaidia University, Souk Ahras - GHRARA Nour El Houda (My University, 2024)
Abstract The study investigates the impact of using audiovisual aids on improving vocabulary retention among first-year EFL students in the English Department at the University Mohammed Cherif Messaadia, Souk Ahras. the research aims to improve learners' vocabulary proficiency, engagement, and ability to effectively remember new words. The study hypothesizes that if audio-visual aids are effectively integrated into English vocabulary instruction, EFL students will demonstrate improved learning and retention of new words. The study was conducted through an exploratory descriptive research, utilizing a mixed method to collect both quantitative and qualitative data, by adapting a triangulation approach data. A quasi-experimental design is adopted with a non-randomized sample of thirty first year students divided into a control group and an experimental group. A questionnaire was administered to eighty students (n=80) to gather additional quantitative data, and qualitative data was obtained through interviews with four teachers of oral expression. The study findings indicated a positive response and significant interest from all participants. The results reveal learners' satisfaction with their experience of learning through audio-visual aids, as they demonstrated that such materials are an effective technique for enhancing vocabulary retention. The results from teachers' interviews indicate that audio-visual aids help learners to enhance and improve their vocabulary acquisition and boost learners' motivation and engagement. Finally, based on the findings, some recommendations and pedagogical implications are suggested to help teachers in integrating audio-visual aids as a part of their classroom instruction. ----------------------- الملخص  دراسة تحقق في تأثير استخدام المساعدات السمعية البصرية على تحسين احتفاظ الطلاب بالمفردات بين طلاب السنة الأولى في قسم اللغة الإنجليزية بجامعة محمد الشريف مساعدية، سوق أهراس. تهدف الدراسة إلى تحسين كفاءة المتعلمين في المفردات والمشاركة والقدرة على تذكر الكلمات الجديدة بفعالية. تفترض الدراسة أنه إذا تم دمج المساعدات السمعية البصرية بفعالية في تعليم مفردات اللغة الإنجليزية، فسيظهر طلاب EFL تحسنًا في تعلم الكلمات الجديدة والاحتفاظ بها. أجريت الدراسة من خلال بحث وصفي استكشافي، باستخدام طريقة مختلطة لجمع البيانات الكمية والنوعية، من خلال تكييف نهج البيانات المثلثة. تم اعتماد تصميم شبه تجريبي مع عينة غير عشوائية من ثلاثين طالبًا من السنة الأولى مقسمة إلى مجموعة ضابطة ومجموعة تجريبية. تم توزيع استبيان على ثمانين طالبًا (ن = 80) لجمع بيانات كمية إضافية، وتم الحصول على بيانات نوعية من خلال مقابلات مع أربعة معلمين للتعبير الشفوي. أشارت نتائج الدراسة إلى استجابة إيجابية واهتمام كبير من جميع المشاركين. تكشف النتائج عن رضا المتعلمين عن تجربتهم في التعلم من خلال المساعدات السمعية البصرية، حيث أظهروا أن هذه المواد هي تقنية فعالة لتعزيز الاحتفاظ بالمفردات. تشير نتائج مقابلات المعلمين إلى أن المساعدات السمعية البصرية تساعد المتعلمين على تعزيز وتحسين اكتساب المفردات وزيادة دافعية المتعلمين ومشاركتهم. أخيرًا، بناءً على النتائج، يتم اقتراح بعض التوصيات والآثار التربوية لمساعدة المعلمين في دمج المساعدات السمعية .البصرية كجزء من تعليمهم في الفصل الدراسي ---------------------- Résumé: L'étude examine l'impact de l'utilisation d'aides audiovisuelles sur l'amélioration de la rétention du vocabulaire chez les étudiants de première année en anglais langue étrangère (EFL) du département d'anglais de l'Université Mohammed Cherif Messaadia, à Souk Ahras. Les chercheurs se concentrent sur l'amélioration de la maîtrise du vocabulaire, de l'engagement et de la capacité des apprenants à se souvenir efficacement de nouveaux mots. L'étude émet l'hypothèse que si les aides audiovisuelles sont intégrées de manière efficace dans l'enseignement du vocabulaire anglais, les étudiants EFL démontreront une amélioration de l'apprentissage et de la rétention des nouveaux mots. L'étude a été menée à travers une recherche descriptive exploratoire, utilisant une méthode mixte pour collecter des données quantitatives et qualitatives, en adaptant une approche de triangulation des données. Un plan quasi expérimental est adopté avec un échantillon non randomisé de trente étudiants de première année répartis en un groupe témoin et un groupe expérimental. Un questionnaire distinct est administré à quatre-vingts étudiants (n=80) pour recueillir des données quantitatives supplémentaires, et des données qualitatives sont obtenues à travers des entretiens avec quatre professeurs d'expression orale. Les résultats de l'étude ont indiqué une réponse positive et un intérêt significatif de tous les participants. Les résultats ont révélé la satisfaction des apprenants avec leur expérience d'apprentissage à travers les aides audiovisuelles, car ils ont démontré que de tels supports sont une technique efficace pour améliorer la rétention du vocabulaire. Les résultats des entretiens avec les enseignants ont indiqué que les aides audiovisuelles aident les apprenants à améliorer et à perfectionner leur acquisition du vocabulaire et à stimuler leur motivation et leur engagement. Enfin, sur la base des résultats, des recommandations et des implications pédagogiques sont suggérées pour aider les enseignants à intégrer les aides audiovisuelles dans leur enseignement en classe.